Loss aversion and mental accounting: the favorite longshot bias in parimutuel betting - Jianying Qiu (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
Parimutuel betting markets are simplified financial markets, and can thus provide a clearer view of pricing issues which are more complicated elsewhere. Though empirical studies generally conclude that the parimutuel betting markets are surprisingly efficient, it is also found that for horses with lowest odds (favorites), market estimates of winning probabilities are smaller than objective winning probabilities; for horses with highest odds (longshot), the opposite is observed. This phenomenon, called the favorite longshot bias, has many explanations such as risk seeking preference, transaction costs, and non-linear transformation of probabilities into decision weights, etc. This paper combines loss aversion with mental accounting, and provides a new explanation for the favorite longshot bias. We show that the bias exists in the absence of all above mentioned reasons, and the degree of the bias differs depending on the type of the mental accounting process that bettors apply.
Keywords: C72; D40; D81; G10; 330; loss aversion; mental accounting; parimutuel betting; the favorite longshot bias; Verlust; Risikoaversion; Glücksspiel; Prospect Theory; Bias; Nichtkooperatives Spiel; Theorie